Fibre laser cutting: the use of carbon-filled acrylic as a qualitative and quantitative analysis tool - Atiyah, H.; Powell, J.; Petring, D.; Stoyanov, S.; Voisey, K.T. (Laser Institute of America, 2018)
The use of carbon filled black acrylic (CFBA) as a quantitative and qualitative analytical tool for fibre laser cutting is investigated. In the qualitative work CFBA targets placed below the laser cutting zone when cutting stainless steel showed a distinctive ‘leaf’ shaped evaporation crater which can provide information about the nature of the reflections taking place in the cut zone. Quantitative measurements have revealed a specific evaporation energy of 3.4J/mm3 for CFBA. However, this figure is only applicable when considering intense beams when the CFBA target is stationary with respect to the laser beam.